2012
DOI: 10.1111/j.1445-2197.2011.05965.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of patient information concerning casts applied post‐fracture

Abstract: Patient recall of information concerning cast care and possible complications was no more than 60%. The provision of written information was associated with a significantly higher awareness of possible complications. The results indicate that for fracture care, the delivery and use of information protocols can be greatly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Most of the studied group was male, married and about one-third were illiterate. These results were consistent with (Hossieny and smith, 2012) [14] who reported that most admitted cases of limbs fractures were aged (18-42 years and the vast majority of them were male but inconsistent with (Delasobera et al, 2015) [6] who founded in his study that more than half of admitted cases with fractures managed with orthopedic plaster casts were elderly people with the highest percentages for females. Researchers view this might be due to several factors putting elders at greater risk for falling and fractures as; age-related changes affect musculoskeletal system in which there is reduction in muscle strength and bone density, low absorption of calcium with aging, as well as multiple pregnancies and lactation for women, reduction of estrogen hormone and increased incidence of osteoporosis for them.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most of the studied group was male, married and about one-third were illiterate. These results were consistent with (Hossieny and smith, 2012) [14] who reported that most admitted cases of limbs fractures were aged (18-42 years and the vast majority of them were male but inconsistent with (Delasobera et al, 2015) [6] who founded in his study that more than half of admitted cases with fractures managed with orthopedic plaster casts were elderly people with the highest percentages for females. Researchers view this might be due to several factors putting elders at greater risk for falling and fractures as; age-related changes affect musculoskeletal system in which there is reduction in muscle strength and bone density, low absorption of calcium with aging, as well as multiple pregnancies and lactation for women, reduction of estrogen hormone and increased incidence of osteoporosis for them.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding patient's knowledge about orthopedic cast care, the current study illustrated that there was a highly statistically significant improvement in patient's knowledge regarding all items about cast care post one week of intervention. These results inconsistent with (Hossieny and smith, 2012) [14] who conducted a study on 109 patients to examine the effectiveness of self-instructional module on www.nursingjournal.net knowledge regarding cast safety at University of Notre Dame and results showed that the post-test knowledge score (60.4%) was significantly higher than the pre-test knowledge score (32.7%). Also the main findings of this study that there was a significant improvement in reported self-care practices about cast care.…”
Section: Discussionmentioning
confidence: 75%
“…Prior studies have shown that providing written cast care instructions is associated with increased patient recall and awareness compared with verbal instructions only. 9 The primary strength of this study was use of an extensive and easily verifiable electronic medical record, which provided detailed information on patient-provider interactions including contact via Internet, telephone, visits, and readmissions. Several limitations should also be noted.…”
Section: Discussionmentioning
confidence: 99%
“…To develop an understanding of one's own illness, its developmental mechanisms, and its associated measures, an indication‐specific education is necessary . The content should always be based on the individual needs of the patient . Patient brochures are a useful supplement to patient education .…”
Section: Introductionmentioning
confidence: 99%
“…The content should always be based on the individual needs of the patient . Patient brochures are a useful supplement to patient education . They have been proven to be an effective medium to increase patients' satisfaction and adherence and may contribute to their empowerment .…”
Section: Introductionmentioning
confidence: 99%